Comfort of the patient's family in an Intensive Care Unit related to welcoming - Mariana de Almeida Moraes Gibaut; Luisa Mayumi Rocha Hori; Katia Santana Freitas; Fernanda Carneiro Mussi (SciELO, 2013)
This study aimed to identify the level of comfort of families of patients in a critical health condition related to the welcoming practices performed by the hospital staff. Interviews were conducted with 250 relatives in hospitals of the state Bahia, using a Likert scale. Data were analyzed as percentages and quartiles. For nine of the 12 statements of the scale, most relatives scored their comfort level between very and totally comfortable, median of 4,revealing kindness, tranquility and friendly communication with family members. More than half of the sample scored its level as not at all to more or less comfortable, median of 3, for statements about demonstration of interest towards the relative by the staff and flexible visiting of the patient. The necessity of greater interest of the team in the condition and needs of the family was observed. Promoting comfort from the dimension of welcoming demands interdisciplinary actions grounded in humanistic philosophy, in which the nurse has an important role to play.